Absence of an aging‐related increase in fiber type grouping in athletes and non‐athletes. (28th August 2020) - Messa, Guy A. M.; Piasecki, Mathew; Rittweger, Jörn; McPhee, Jamie S.; Koltai, Erika; Radak, Zsolt; Simunic, Bostjan; Heinonen, Ari; Suominen, Harri; Korhonen, Marko T.; Degens, Hans
Abstract : The aging‐related loss of muscle mass is thought to be partly attributable to motor neuron loss and motor unit remodeling that result in fiber type grouping. We examined fiber type grouping in 19‐ to 85‐year‐old athletes and non‐athletes and evaluated to which extent any observed grouping is explained by the fiber type composition of the muscle. Since regular physical activity may stimulate reinnervation, we hypothesized that fiber groups are larger in master athletes than in age‐matched non‐athletes. Fiber type grouping was assessed in m. vastus lateralis biopsies from 22 young (19‐27 years) and 35 healthy older (66‐82 years) non‐athletes, and 14 young (20‐29 years), 51 middle‐aged (38‐65 years), and 31 older (66‐85 years) athletes. An "enclosed fiber" was any muscle fiber of a particular type surrounded by fibers of the same type only. A fiber type group was defined as a group of fibers with at least one enclosed fiber. Only type II fiber cross‐sectional area (FCSA) showed an age‐related decline that was greater in athletes ( P  < .001) than in non‐athletes ( P  = .012). There was no significant age‐related effect on fiber group size or fiber group number in athletes or non‐athletes, and the observed grouping was similar to that expected from the fiber type composition. At face value, these observations do 1) neither show evidence for an age‐related loss and remodeling of motor units nor 2) improved reinnervation with regular physical activity, but 3) histological examination may not reveal the full extent of aging‐related motor unit remodeling.